Inhibitory effects of total triterpenoids isolated from the Hedyotis diffusa willd on H1975 cells - Kenan Wu; Xue Wu; Yanni Liang; Ting Wang; Dongzhi Wu; Luhan Li; Zheng Wang (Frontiers Media S.A., 2022)
It is estimated that non-small-cell lung cancer (NSCLC) is responsible for 80% of human deaths related to lung cancer worldwide. Currently, it has been discovered that two transcription factors. Nuclear factor-κB (NF-κB) and Signal transducer and activator of transcription 3 (STAT3) were the main factors affecting inflammation and cancer, and their activation promoted lung cancer cell proliferation. Hedyotis diffusa Willd. (H. diffusa) is an herbal Chinese medicine, which has always been used for the treatment of malignant tumors in clinical. Previous research found that H. diffusa could inhibit the proliferation of H1975 cells, but the specific mechanisms remain elusive. We investigated the effects of total triterpenes extracted from H. diffusa (TTH) on the migration, proliferation and apoptosis of H1975 cells. Cell-cycle and immunofluorescence analysis showed that TTH could block H1975 cells at G0/G1 phase and induce apoptosis of experimental cells. The protein levels of Bcl-2 were decreased, while the levels of pro-apoptotic Bax were increased. In addition, TTH could also inhibit the migration of H1975 cells through downregulated MMP-2 and MMP-9 and upregulated TIMP-2. Further research found that the level of phospho-STAT3 was significantly decreased after administration of TTH. And protein expression level of NF-κB in nucleus was decreased after TTH treatment, while NF-κB in cytoplasm increased. These results suggested that TTH could inhibit the proliferation and migration of H1975 cells, and also could induce cell apoptosis. These effects were closely connected to the activation of NF-κB and the phosphorylation of STAT3.